The Role Of Parents In Instilling Islamic Character In Children - Diah Pahmasari Harahap; Annisaturrahmi (Genderang Asa: Journal of Primary Education, 2026)
Islamic character education within the family plays a strategic role in shaping children’s moral and spiritual development amid the challenges of modern life, particularly rapid digitalization and changing parenting patterns. Parents, as the first and primary educators, bear significant responsibility in instilling Islamic values through role modeling, habituation, and daily interactions. This study aims to systematically examine the role of parents in instilling Islamic character in children, the strategies employed, and the challenges encountered in contemporary contexts.This study employs a literature review method with a qualitative descriptive approach. The data sources consist of nationally accredited SINTA journals, reputable international journals, scholarly books, and relevant academic documents published between 2015 and 2024. Data were collected through a systematic literature search across several academic databases and analyzed using content analysis techniques, including data reduction, data presentation, and thematic conclusion drawing.The findings indicate that the parental role in instilling Islamic character in children encompasses five main dimensions: role modeling (uswah hasanah), habituation of worship practices, value-based communication, digital supervision and parenting, and emotional–spiritual support within the family. Parental role modeling and worship habituation emerged as the most influential factors in shaping children’s character. Furthermore, digital challenges require parents to adopt adaptive and dialogical Islamic parenting strategies. This study concludes that Islamic character education within the family requires a holistic approach that integrates behavioral, habitual, emotional, and spiritual dimensions simultaneously. The findings are expected to contribute theoretically to Islamic education studies and practically to guide parents in fostering Islamic character in children in the modern era.